(untitled) (GAIMS Journal of Medical Sciences, 2026)
Adenoid cystic carcinoma (ADCC) is an uncommon malignant tumor of the salivary glands, often involving the palate. It is notorious for its indolent yet infiltrative behavior, characterized by perineural invasion and late recurrences. Its presentation may overlap with benign odontogenic lesions, creating diagnostic dilemmas. A 40-year-old male presented with a 6-month history of swelling, pain, and tooth mobility in the left maxillary region, accompanied by occasional bleeding. Computed tomography revealed a multilocular hypodense lesion extending from the left maxilla to the palate with bone destruction. Radiological impression suggested an odontogenic tumor. Histopathological examination of an incisional biopsy confirmed adenoid cystic carcinoma, cribriform type. The patient underwent partial maxillectomy with adjuvant radiotherapy. ADCC in the minor salivary glands can radiographically resemble ameloblastoma or other multilocular lesions, leading to potential misdiagnosis. Histopathology remains the cornerstone for diagnosis, grading, and prognosis determination. Radical surgical excision with tumor-free margins combined with postoperative radiotherapy offers the best control. Long-term surveillance is essential due to its unpredictable late metastasis. Palatal lesions with multilocular radiolucency warrant histopathological confirmation before definitive management. Early detection and multidisciplinary treatment planning are vital for improving survival outcomes.